Isolated ventricular septal defect. A case report - Monzón Castillo, Eli Pedro (2020)
Congenital heart disease is the most common congenital anomaly. Ventricular septal defect (VSD) is a frequent congenital heart disease in newborns, affecting 25 to 30% neonates with cardiac defects. Muscular VSDs are more frequent than perimembranous VSDs. The association of cases with chromosomal anomalies and isolated VSD is relatively low. Spontaneous closure of isolated VSD is higher with small VSD cases, and the muscular VSD is more likely to close spontaneously than the membranous or perimembranous types. Therefore, diagnosis of isolated muscular VSD with no other anomalies can be considered a benign finding.